A Ming Society : T'ai-ho County, Kiangsi, in the Fourteenth to Seventeenth Centuries - Dardess, John W. (University of California Press, 2023)
John Dardess has selected a region of great political and intellectual importance, but one which local history has left almost untouched, for this detailed social history of T'ai-ho county during the Ming dynasty. Rather than making a sweeping, general survey of the region, he follows the careers of a large number of native sons and their relationship to Ming imperial politics. Using previously unexplored primary sources, Dardess details the rise and development of T'ai-ho village kinship, family lineage, landscape, agriculture, and economy. He follows its literati to positions of prominence in imperial government. This concentration on the history of one county over almost three centuries gives rise to an unusually sound and immediate understanding of how Ming society functioned and changed over time. This title is part of UC Press's Voices Revived program, which commemorates University of California Press's mission to seek out and cultivate the brightest minds and give them voice, reach, and impact. Drawing on a backlist dating to 1893, Voices Revived makes high-quality, peer-reviewed scholarship accessible once again using print-on-demand technology. This title was originally published in 1996.